Prevalence of re-laparotomy and its risk factors in patients who underwent gastrointestinal procedure at Referral Hospital in Ethiopia - Kumlachew Geta; Amsalu Molla; Yonas Kassaw; Simegnew Kibret; Metages Hunie; Kaletsidk Dessalegn; Diriba Teshome; Belayneh Dessie; Keder Essa; Efrem Fenta (PLoS ONE, 2026)
Background Re-laparotomy is one of the causes of morbidity and mortality among patients who have had abdominal surgery. Due to the unavailability of laparoscopic surgery in the region, laparotomy remains the standard treatment. As a result, re-laparotomy is commonly performed, significantly increasing the labor load, financial costs, and the risks of morbidity and mortality for patients. The aim of this study is to evaluate the prevalence and factors associated with re-laparotomy procedures, in order to better understand their impact on patient health and healthcare resources. Methods A retrospective cross-sectional study was conducted on patients who underwent gastrointestinal procedures in a hospital in Ethiopia between September 2020 and August 2022. The association between independent variables with re-laparotomy (dependent variable) was analyzed using bi-variate and multivariate logistic regression. Those variables that had a p-value of less than 0.2 were put into a multivariate analysis. The strength of the association was displayed using crude and adjusted odds ratios with a 95% confidence interval. P-values less than 0.05 were used to determine statistical significance. Results A total of 1276 charts were reviewed, and 127 (10%) of those were found to have re-laparotomy. A greater proportion of re-laparotomy was associated with the occurrence of prior abdominal surgery (AOR = 67.94, 95% CI: 39.07, 118.13), the existence of ischemic bowel during surgery (AOR = 4.36, 95% CI: 2.10, 9.02), and the intraoperative use of inotropic/vasopressor medications (AOR = 7.03, 95% CI: 2.52, 19.59). Conclusions The prevalence of re-laparotomy was found to be 10% which is higher compared with some previous reports. Prior abdominal surgery, ischemic bowel presence during surgery, and the use of inotropic/vasopressor drugs intra-operatively were all found to be risk factors for re-laparotomy.